2020
DOI: 10.1186/s12889-020-8267-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of diabetes mellitus, pre-diabetes, undiagnosed and uncontrolled diabetes in Central Iran: results from Yazd health study

Abstract: Background: Over the past few decades, the prevalence of Diabetes Mellitus (DM) has risen rapidly in Iran and other low and middle-income countries. We investigated the prevalence of DM, pre-diabetes, undiagnosed and uncontrolled diabetes and its relationship with some associated socioeconomic factors in the Yazd Greater Area in Iran. Methods: Yazd Health Study is a longitudinal study conducted to determine the prevalence of non-communicable disease and related risk factors. In a two-step cluster sampling, 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
111
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 27 publications
13
111
2
1
Order By: Relevance
“…According to a report by World Health Organization (WHO), Yazd city, a world heritage city located in center of Iran, has the highest prevalence (14.9%) of T2DM based on hemoglobin A1c (HbA1c) among all cities of Iran. 12,13 The aim of the present study was to describe the HRQoL of patients with T2DM by Iranian EQ-5D-5L in Yazd province and analyze the impact of sociodemographic and clinical factors on HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by World Health Organization (WHO), Yazd city, a world heritage city located in center of Iran, has the highest prevalence (14.9%) of T2DM based on hemoglobin A1c (HbA1c) among all cities of Iran. 12,13 The aim of the present study was to describe the HRQoL of patients with T2DM by Iranian EQ-5D-5L in Yazd province and analyze the impact of sociodemographic and clinical factors on HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in 2011 almost 11.9% of Iranian adults had diabetes, which is almost 35% higher than in 2005. It is also estimated that in 2030, about 10 million of Iranian people will develop diabetes (Mirzaei, Rahmaninan, Mirzaei, Nadjarzadeh, & Dehghani tafti, 2020). In general, the detrimental effects of hyperglycemia are divided into macrovascular complications (coronary artery disease, peripheral artery disease, and stroke) and microvascular complications (diabetic nephropathy, neuropathy, and retinopathy) (Fowler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes in adults in the member states of the World Health Organization of the Eastern Mediterranean (EMRO) is reported to be 13.7%. This is the highest prevalence among other WHO regions [2]. In Iran, the prevalence of diabetes in adults within the age range of 25-70 has been reported to be 11.9% (2011).…”
Section: Introductionmentioning
confidence: 98%